2010
DOI: 10.1542/peds.2008-2720
|View full text |Cite
|
Sign up to set email alerts
|

“My Child Doesn't Have a Brain Injury, He Only Has a Concussion”

Abstract: Children with mild traumatic brain injuries have an increased frequency of receiving the concussion label, although the label may also be applied to children with more-severe injuries. The concussion diagnosis is associated with important clinical outcomes. Its typical use in hospital settings likely refers to an impact-related mild brain injury, in the absence of indicators other than a loss of consciousness. Clinicians may use the concussion label because it is less alarming to parents than the term mild bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 32 publications
(26 reference statements)
0
53
1
Order By: Relevance
“…100 Second, concussions are easily neglected under a popular belief that the neurologic symptoms have an obvious cause, will resolve quickly, leave nothing visible on medical imaging and do not require follow-up. 101,102 Third, concussions are rarely deemed relevant for consideration by psychiatrists or other physicians when eliciting a patient's history. 103,104 Greater attention to the longterm implications of a concussion in community settings might save lives because deaths from suicide can be prevented.…”
Section: Resultsmentioning
confidence: 99%
“…100 Second, concussions are easily neglected under a popular belief that the neurologic symptoms have an obvious cause, will resolve quickly, leave nothing visible on medical imaging and do not require follow-up. 101,102 Third, concussions are rarely deemed relevant for consideration by psychiatrists or other physicians when eliciting a patient's history. 103,104 Greater attention to the longterm implications of a concussion in community settings might save lives because deaths from suicide can be prevented.…”
Section: Resultsmentioning
confidence: 99%
“…There is little evidence beyond expert opinion for the ideal cognitive and physical recommendations, and the observed wide practice variation may reflect the lack of high level (level A or B) evidence in this area. 46 A comparative trial is needed for both return-to-activity and return-to-school guidelines to determine the ideal components to improve outcomes after concussion.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] These other studies suggest that individuals view concussion and TBI as separate events and have shown that individuals' understanding of terminology shapes differential expectations of injury outcomes. 36 For example, DeMatteo and colleagues 33 found that labeling an injury a concussion strongly predicted earlier discharge from the hospital and return to school for children with mild TBI, independent of Glasgow Coma Scale score and presence of other associated injuries. In fact, children in that study who received the diagnosis of concussion were 1.5 times as likely to be discharged early and 2.5 times more likely to return to school early than children who received a diagnosis of mild TBI.…”
Section: Discussionmentioning
confidence: 95%
“…2. Knowledge about mild TBI: We compiled a list of 33 items assessing the psychological (eg, "feeling irritable or easily annoyed"), cognitive (eg, "trouble concentrating"), and physical symptoms (eg, "nausea/vomiting") characteristic of a mild TBI. Additional subsections included items assessing beliefs about recovery and treatment.…”
Section: Methodsmentioning
confidence: 99%